2020
DOI: 10.1007/s12250-020-00244-z
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally Reprogrammed Human Normal Airway Epithelial Cells at ALI: A Physiological Model for Emerging Viruses

Abstract: Cancer cell lines have been used widely in cancer biology, and as biological or functional cell systems in many biomedical research fields. These cells are usually defective for many normal activities or functions due to significant genetic and epigenetic changes. Normal primary cell yields and viability from any original tissue specimens are usually relatively low or highly variable. These normal cells cease after a few passages or population doublings due to very limited proliferative capacity. Animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…It has been reported that cr increases the proliferative capacity of pAECs compared with conventional culture techniques ( 36 , 37 , 41 ). To confirm this effect in our experimental setup, population doublings were determined in pNECs cultured under conventional or cr conditions, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cr increases the proliferative capacity of pAECs compared with conventional culture techniques ( 36 , 37 , 41 ). To confirm this effect in our experimental setup, population doublings were determined in pNECs cultured under conventional or cr conditions, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primary NECs (pNECs) can be obtained noninvasively from both healthy and diseased subjects for research purposes ( 32 35 ) and display a useful model to study the pathogenesis of infectious and inflammatory airway diseases. Recently, NEC cultures have been discussed as a suitable model to study aspects of SARS-CoV-2 infection ( 36 ). A major limitation for such studies is the relatively small cell number obtained from single donors via nasal brushings.…”
Section: Introductionmentioning
confidence: 99%
“…Upon isolation, these cells are cultured and differentiated on porous supports at an air-liquid interface (ALI), in which the apical side is in contact with air. HAE cells represent a complex tissue with differentiated ciliated, goblet and basal cells and retain the highest similarity to human airway epithelium physiological conditions found in vivo [34,35]. HAE cells were used to isolate and discover SARS-CoV-2 for the first time upon its emergence in Wuhan, China.…”
Section: D-cell Models: Explants and Organoidsmentioning
confidence: 99%
“…Cellular models based on HAE offer similarity to physiological conditions and maintain many of the important markers and functions from the donor tissue [35]. Despite the great advantages of using primary cells, mainly regarding more realistic virus-host interactions, models based on immortalized cell monolayers are easy to use, less time-consuming and bypass ethical concerns associated with the use of animal and human tissue [34].…”
Section: D-cell Models: Explants and Organoidsmentioning
confidence: 99%
“…This may reflect an inherent restriction of goblet cell hyperplasia to the lower airways in asthma but is an important consideration in terms of model selection. Nasal cell cultures have been used in the study of viral entry, receptors and internalization, viral replication and innate immune responses [ 89 ]. Studies using paired nasal and bronchial cell cultures have shown similar antiviral and viral induced pro-inflammatory responses between to the two tissue sources [ 90 ].…”
Section: Introductionmentioning
confidence: 99%